Project of the Modern Classification of the Food Hypersensitivity Clinical Symptoms in Сhildren - S.M. Nedelska; O.P. Pakholchuk (Zaslavsky O.Yu., 2016)
Actuality. Food hypersensitivity (FH) remains an important problem of the childhood that has medical and social sides. For the decades, classification of FH skin manifestations is based on the combination of not clear pathophysiological and clinical signs and is caused by insufficient use of the method of morphological determination of rash elements and its comparison with a past medical history. Objective. To propose updated definitions and the project of classification of clinical manifestations of food hypersensitivity that will enable to improve clinical significance, to identify targets of possible therapeutic intervention at different pathogenetic mechanisms of FH, to increase the efficacy of clinical diagnostics, to develop common approaches to the data interpretation. Materials and methods. Advanced review of the literature sources, both paper and electronic (including Medline and the Cochrane Library, 2010-2016), as well as the results of own researches served as the basis for the creation of the project. Results. The current classification of FH is ambiguous and reflects the lack of understanding of the nature of the disease, which may have immune and non-immune mechanisms. Problems with verifying the diagnosis are also due to the fact that the same symptom in the skin can occur at different pathophysiological mechanisms of development, that is why it is important to take into account anamnesis and subjective symptoms, which differ in specific forms of FH. The article offers the draft classification of clinical manifestations of FH, based on recent literature data and the results of own observations. Target organ and pathogenetic mechanism, some morphological elements are taken as the basis. Conclusions. The proposed method will improve the clinical significance and make it possible to create a unified approach to the data interpretation.